The numerical analysis of cracks development under nonuniform settlements of a construction - Bartolomey, Maria Leonidovna (Computational Continuum Mechanics, 2012)
We investigate the stress-strain state of a three-dimensional construction at the given settlements of columns. In the framework of the theory of bending plates and rectilinear rods, a dangerous area in the floor plate has been revealed. A three-dimensional model has been developed for this area of the plate, which allows us to determine the damage level of the floor plate material. The values of settlements at which the first cracks appear in the examined segment of the construction have been obtained